A block-based Markov random field model estimation for contextual classification using Optimum-Path Forest - Osaku, Daniel (2016)
Contextual image classification aims at considering the information about nearby samples in the learning process in order to provide more accurate results. In this paper, we propose a locally-adaptive Optimum-Path Forest classifier together with Markov Random Fields (MRF) that surpasses its naïve version, which was recently presented in the literature. The experimental results over four satellite images demonstrated the proposed approach an outperform previous results, as well as it can perform MRF parameter learning much faster than its former version.